ANALISIS PENGELOLAAN PIUTANG PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI BPKAD KOTA MAGELANG PERIODE 2018-2022 - Palupi, Rani Mulia; Fathah, Rigel Nurul (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2024)
Abstract : This study aims to analyze the management of Rural and Urban Land and and Building Tax receivables (PBB-P2) at the Regional Finance and Asset Management Agency of Magelang Municipality for the period 2018-2022. The research was qualitative research. Data were collected from interviews and reports of PBB-P2 for the period 2018-2022. Interviews were conducted using structured techniques with resource persons for the Head of Revenue Determination and Administration Sub-Division, Head of Reporting Sub-Division, Regional Tax and Retribution Analyst, and Head of Tax Registration and Data Collection Sub-Division. The data analysis technique used qualitative descriptive and data processing from interviews. The results of the study show that PBB-P2 receivables in Magelang Municipality have increased every year. Especially in 2020, 2021 to 2022. BPKAD Magelang Municipality has implemented several programs as an effort to collect PBB-P2 receivables but is still constrained by limited human resources and efforts to collect receivables are not intensive enough. Keywords : Tax Receivables, Land and Building Tax, Tax Receivables Management